DAMPAK PEMBERIAN KALSIUM TERHADAP TEKANAN DARAH IBU HAMIL DI BOGOR - Dewi Permaesih; Reviana Christiani; Yuniar Rosmalina; Ance Murdiana Dahro; Rossi R.S. Apriyantono; S. Hendra; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1999)
The Effect of Food Calcium Supplementation on the Blood Pressure Level of Pregnant Women in Bogor District.Study on the calcium supplementation to prevent the increase of blood pressure level of pregnant women was conducted in 6 Community Health Centers in Bogor District. Seventy-seven pregnant women between 18-23 weeks of pregnancy were included in this study. They were randomly assigned to receive 2 kinds of food (biscuit and syrup) which contain 700 mg of calcium for the intervention group and 200 mg for the control group. The subjects were asked to consume every 5 days in a week for 16 weeks. The results shows that no significant different in body weight, clinical status and biochemical status, calcium in urine and feces between 2 group. The energy and calcium intake were still below the indonesian RDA level. Diastolic blood pressure in supine position was decreased by 1.4 mg Hg in intervention group and 0.9 mg Hg in control group after 16 weeks of the study. However there was no significant difference between intervention and control group. This study observed there was a tendency that calcium supplementation maintains diastolic blood pressure level.Keywords: calcium, blood pressure, pregnant women.